Analyzing intelligence origins, obstacles, and innovations - George, Roger Z. 1949-; Bruce, James B (Georgetown University, 2008)
Presents an assessment of the state of intelligence analysis since 9/11. This book includes a critique of why it has under-performed at times. It provides insights regarding the enduring obstacles as well as challenges of analysis in the post-9/11 world, and suggests ideas for improved analytical methods, training, and structured approaches.